The Role Of Engagement Leadership And Motivation In Pharmaceutical Companies During Pandemic Covid-19 - Krisna Wahyu Nugraha; Noermijati Noermijati; Nanang Suryadi (Politeknik APP Jakarta, 2022)
This study aimed to determine the mediating role of employee engagement in the relationship between transformational leadership and motivation on employee performance. Questionnaires were used to collect data from employees of companies operating in the pharmaceutical sector in Jakarta with 223 respondents. The data analysis used structural equation modeling with Smartpls program. The results of the study showed that transformational leadership directly can increase employee performance and work engagement. Furthermore, motivation was able to increase job engagement but it was not able to increase performance. Interestingly, employee engagement had been able to fully mediate the effect of motivation on employee performance, but it was unable to mediate the effect of transformational leadership on performance.